An audit of transfers into the PICU at the Red Cross War Memorial Children's Hospital: a follow up study - Dimitriades, Konstantinos (University of Cape Town, 2016)
Background: Children are transferred from various facilities into the paediatric intensive care unit (PICU) at the Red Cross War Memorial Children's Hospital for critical care, without a specialised paediatric transfer service. A previous audit in 2003 reported a high incidence of technical, clinical and critical adverse events during transfers. Objective: To conduct a follow -up audit on interfacility transfers into PICU to determine practice and outcome changes. Methodology: Prospective observational study of all patients transferred into PICU between 1 Dec ember 2013 and 30 November 2014 and compared to the 2003 audit by Hatherill et al. Results: Analysis was performed on 204 transfers (median (IQR) age 1.8 (0.2 – 12.6) months and compared to results reported by Hatherill et al (2003). The proportion of medical transfers decreased (49% to 34.3% p=0.003) as well as the referrals from metropolitan hospitals (34.7% to 17.6%, p = 0.0001), whilst the number of referrals from academic hospitals increased from 35.1% to 44.6% (p = 0.05). Staff accompanying transfers and transfer times remained unchanged. The proportion of fixed wing transfers increased from 14.4% to 25.5% (p=0.006) whilst Helicopter transfers decreased from 9.9% to 1% (p <0.0001). 58.4% of patients were in tubated for transfer in 2003 compared to 69.1% in 2014 (p = 0.02). The rate of technical (35.6% to 39.7%, p = 0.4), clinical (26.7% to 31.9%, p = 0.25), and critical (8.9% to 8.8%, p = 0.97) adverse events remained unchanged. PICU Mortality decreased from 16.8% to 9.45% (p=0.03) with a decrease in Standardized Mortality Rate from 1.11 to 0.68. Three children died on arrival to PICU. The communication tool was used in 45.1% of transfers and its use was noted to be associated with significantly less critical adverse events (4.3% vs. 12.5%, p = 0.048). Technical adverse events were positively correlated with the clinical adverse events (Spearman's R = 0.3; p=0.000008) and critical adverse events (Spearman's R = 0.1; p = 0.03). In turn the total number of clinical adverse events were positively correlated with the total number of critical adverse events (Spearman's R = 0.5; p < 0.000001). The multiple regression analysis for PICU mortality found the total number of clinical adverse events to be independently associated with ICU mortality (adjusted OR 95% CI 2.8 (1.7 -4.7); p = 0.0001) Conclusion: The rate and staffing structure of interfacility transfers into PICU have remained unchanged, and associated adverse event rates remain high. Changes are noted in the profile of transferred patients as well as adverse events. Efforts to formalize the paediatric transfer service must be strengthened whilst using interim measures to improve the current standard through education, improved skills and PICU support.